Reputation Shocks and Strategic Responses in Electoral Campaigns - Rubén Poblete Cazenave (Tinbergen Institute, 2021)
Information affecting a candidate's reputation might have significant electoral consequences. Do candidates respond to the release of information? Using Brazilian elections and audits as an exogenous source of information, I show that both incumbent and challenger increase their campaign spending when detrimental information affects the incumbent's reputation. Conversely, beneficial information decreases candidates' spending. The main channel is that information affects the expected competitiveness of elections and, therefore, candidates' spending. Only information disclosed prior to electoral campaigns impacts campaign spending. Furthermore, incumbents also adapt a conditional cash transfers program by increasing (decreasing) the beneficiaries when detrimental (beneficial) reputation shocks occur.
Keywords: D72; D73; D83; P16; 330; Information; Politicians' reaction; Campaign spending; Elections; Corruption